Multimedia interaktif bagi guru Pendidikan Anak Usia Dini di Kabupaten Gowa - Udin Sidik Sidin; Ahmad Wahyuddin Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Science and Technology Activity(IbM) aims to help teachers in schools to improve theirprofessionalism in the teaching and learning process. they aretrained in designing learning media that can be implemented inlearning activities. The method used in the activity is to sharemodules as references, lecture methods and question andanswer. Participants are given basic mastery of learning mediadesign about understanding, supporting facilities andinfrastructure. the method used is a practice method bytraining participants to know the internet network and usingthe software provided to build learning media, practicing worksteps according to the modules that are shared. The resultsachieved from this activity are that participants haveunderstood the principles of designing the media that will beused in the teaching and learning process, and know thesupporting facilities and infrastructure to design a media that isused evaluation of the implementation of the activity obtaineda mean score of 3.87 with the criteria of very good.